Novel approach for mold filling simulation of the processing of natural fiber reinforced composites by resin transfer molding - Francucci, Gaston Martin (2013)
Modeling the infiltration of reinforcements during the processing of composite materials by liquid composite molding techniques is an important instrument for the prediction of flow front patterns, filling times and pressure gradients. Darcy’s law is widely used to model most of these processes. However, when polar fluids are used together with natural fibers, fiber swelling may occur and introduce further complexity to the simulation. In this work, a model that includes the aforementioned phenomena is proposed, leading to a more accurate prediction of the flow front position than the classic models that use a constant permeability value.